Nürnbergi kohtualuste autograafid Eesti sõjamuuseumi – kindral Laidoneri muuseumi kogudes [Autographs of Nuremberg Defendants in the Collections of the Estonian War Museum – General Laidoner Museum] - Lätte, Mart (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2011)
In the early summer of 2007, a collection of the autographs of various defendants at the Subsequent Nuremberg Trials arrived in Estonia, from Canada, having been donated to the collections of the Estonian War Museum. This autograph collection had belonged to the exile Estonian photographer Evald “Tommy” Tomson (1924–2006). After World War II, Tomson served in Estonian Guard Company 4221, which had been formed by the United States occupation authorities in Germany. This security unit guarded the accused war criminals during the Subsequent Nuremberg Trials. And the autograph collection dates back to this period. After the end of World War II, there were many Estonians, who had fought on the German side, being held in Allied prisoner-of-war camps. They were released during the years 1945–1948 (in the American occupation zone, the last Estonians were released already in 1946). Many of these men found employment in paramilitary guard and labour units, which functioned under the jurisdiction of the U.S. occupation forces in Germany. All together, the Americans recruited four Estonian guard and five labour companies. Guard Company 4221 was established at the end of December 1946. And began to fulfi l its duties in Nuremberg, at the end of February, or the beginning of March 1947. After the Second World War, two international war tribunals were held – one in Nuremberg (International Military Tribunal [IMT] at Nuremberg), the other in Tokyo (IMT for the Far East) – to try the major war criminals. At the Nuremberg IMT, the defendants were indicted under the following four points: 1) conspiracy (the group planning of criminal activity); 2) crimes against peace; 3) war crimes, or the violating of the international laws and conventions of war; 4) crimes against humanity. The defendants at the Tokyo IMT were indicted under points 2 and 3. In addition to this, a great many follow-up trials were held in both Europe and Asia, at which, lesser war criminals, who had, nevertheless, been more personally involved with the crimes, were tried. These subsequent trials were held, in addition to the war tribunals of the four main Allied nations and Germany, also by Holland, Norway, Canada, Greece, China, etc. The Subsequent Nuremberg Trials were conducted by U.S. military tribunals. Th e legal basis for the Subsequent Nuremberg Trials was Law No.10 of the Allied Control Council, according to which, indictments were presented on the basis of the aforementioned points, that had been implemented at the Nuremberg IMT. Plus, there was an additional point concerning membership in the criminal organizations known as the SS (Schutzstaff el), the SD (Sicherheitsdienst), and the Gestapo (Geheime Staatspolizei), as well as in the leadership of the German National Socialist Workers’ Party (Korps der politischen Leiter der NSDAP). The Subsequent Nuremberg Trials lasted from October 1946, until May 1949. All together, 12 trials were held: • The Medical Case • The Milch Case • The Justice Case • The Pohl (or WVHA [Wirtschafts- und Verwaltungshauptamt der SS] Case • The Flick Case • The Farben Case • The Southeast/Hostage Case • The RuSHA (Rasse- und Stedlungshauptamt der SS) Case • The Einsatzgruppen Case • The Krupp Case • The Ministries Case • The High Command (OKW – Oberkommando der Whrmacht) Case Within the framework of these trials, various sentences, some as severe as the death sentence, were handed down, although several of the accused were acquitted. The autographs of the indicted arrived at the Museum in a cardboard box. In addition to the autographs, the box also contained photos, caricatures, and copies of autographs. The autographs were on 56 sheets and altogether the collection consisted of the autographs of about 160 individuals (the exact number of individuals involved cannot be determined, since, in some cases, the handwriting is illegible, and it is not possible to determine if it is an autograph, or part of a longer text). Someone, probably the collector, has pencilled notes onto the sheets bearing the autographs. Some of the autographs also include a dedication, an aphorism, or a wish. But there are also many autographs unaccompanied by any text at all, or just with the signer’s name, former position, and the date. The texts that accompany the autographs tend to be quite similar: Estonians are sent best wishes; the Estonian (Baltic) guards are thanked for the good treatment and sympathy that the prisoners have received; hope and conviction are expressed that Europe, including Estonia and Germany, will one day be free again; etc. All the texts are quite brief. Some of the autograph texts are sentimental, and there are even poems. Many of the writers mention or thank Estonians and the Balts. This may be due to the fact that the guards, most of whom, had served in the German military forces during the war, could communicate with the prisoners, and thus, got along with them, and treated them civilly. But not all of the autographs are those of the accused at the Subsequent Nuremberg Trials. Some are those of witnesses who testified at a trial. And, in some cases, it cannot be determined who the signer is. In the case of some individuals, for instance, the artillery general Curt Gallenkamp, who was found guilty by a British military tribunal, it is not known why they were in Nuremberg at that time. But, it can, nevertheless, be assumed that, even though these individuals do not appear in the lists of the witnesses of the Subsequent Nuremberg Trials, they were, somehow, connected with the Nuremberg process.